2019
DOI: 10.3389/fmicb.2019.02192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Novel Host Protein Interacting With the Structural Protein VP1 of Chinese Sacbrood Virus by Yeast Two-Hybrid Screening

Abstract: Chinese sacbrood virus (CSBV) is the major cause and lead to the collapse of Apis cerana colonies. VP1, the structural protein of CSBV, shows the highest variation in the amino acid sequences among proteins from different CSBV strains as well as exhibits excellent immunogenicity. However, its function with host protein still remains unclear. To clarify its function with host protein, we screened out host cellular proteins that interact with VP1 using the membrane protein yeast two-hybrid system. In addition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…DNA viruses, such as Epstein-Barr virus (6). Because Y2H relies on heterologous expression of cDNA libraries in yeast, it opens up the study of many virus-host protein interactions, even if tractable cell culture models and/or high-quality proteomes are not readily available, as is the case for many viruses that infect arthropods (7,8). Identification of direct one-to-one interactions is biochemically advantageous because it is more likely that the interaction can be dissected in vitro if the interaction is direct.…”
Section: Yeast Two-hybridmentioning
confidence: 99%
“…DNA viruses, such as Epstein-Barr virus (6). Because Y2H relies on heterologous expression of cDNA libraries in yeast, it opens up the study of many virus-host protein interactions, even if tractable cell culture models and/or high-quality proteomes are not readily available, as is the case for many viruses that infect arthropods (7,8). Identification of direct one-to-one interactions is biochemically advantageous because it is more likely that the interaction can be dissected in vitro if the interaction is direct.…”
Section: Yeast Two-hybridmentioning
confidence: 99%
“…The size of VP2 (32 kDa) and VP3 (28 kDa) is similar to that of other picornavirus capsid proteins, and VP2 has been reported to exhibit good immunogenicity ( Fei et al, 2020 ). Previous studies have shown that the structural proteins of Iflavirus are involved in viral invasion and replication ( Brutscher et al, 2016 ; Kalynych et al, 2016 ; Procházková et al, 2018 ; Zhang et al, 2019 ). We speculated that the structural proteins of DWV also exert a similar effect.…”
Section: Introductionmentioning
confidence: 99%
“…Affinity purification methods are based on the specificity of antibody–epitope interaction [ 8 ]. The yeast-2-hybrid (Y2H) [ 9 , 10 ] and synthetic lethality are in vivo techniques. According to Fields and Song [ 11 ], the Y2H is scalable and can be used to evaluate the interaction of several proteins in parallel with some automation.…”
Section: Introductionmentioning
confidence: 99%